2009
DOI: 10.1021/jf9020976
|View full text |Cite
|
Sign up to set email alerts
|

Biorecognition of Chemically Modified Bovine Serum Albumin with Lactose Prepared under Different Conditions

Abstract: Glycoconjugates consist of glycans attached to proteins or lipids. Glycans are involved in important biological functions such as trafficking of glycoconjugates, mediation, and modulation of cell adhesion and signaling. This study was conducted to obtain neoglycoconjugates containing a large number of carbohydrates, added through the condensation of reducing sugars with protein amino groups, whose structures were recognized by lectins. Neoglycoconjugates (BSA-Lac) of bovine serum albumin (BSA) with d-lactose w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Recently, proteins such as serum albumin (porcine and bovine) chemically modified with disaccharides were biorecognized by plant lectins and bacterial adhesins . Furthermore, porcine serum albumin conjugated with lactose could compete in vitro with intestinal bacterial natural ligands .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, proteins such as serum albumin (porcine and bovine) chemically modified with disaccharides were biorecognized by plant lectins and bacterial adhesins . Furthermore, porcine serum albumin conjugated with lactose could compete in vitro with intestinal bacterial natural ligands .…”
Section: Introductionmentioning
confidence: 99%
“…K88 strains of ETEC that cause diarrhea in pigs possess an adhesin essential for disease to occur [ 19 ]. Recent reports show that K88 adhesin targets specific receptors containing galactose exposed when using lactosylated albumin [ 13 , 14 ]. In this study, the formulation of stabilized microspheres, antibiotic carriers, using lactosylated albumin as encapsulation polymer, was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has reported that BSA chemically modified with lactose (BSA-Lac) leads to recognition of piglet pathogens, such as enterotoxigenic Escherichia coli K88, and by carbohydrate-binding proteins from Ricinus communis agglutinin I (RCA I), a galactose specific lectin [ 13 , 14 ]. The aim of this work was to use BSA-Lac as a polymer to obtain lactosylated microspheres (MS-Lac) that carry gentamicin and to stabilize them by crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…This coupling reaction of protein with sugar produces neoglycans. Previous reports indicate that glycation is favored by temperatures above 60°C, alkaline pH, and influenced by moisture and reaction time (Ledesma-Osuna et al, 2009;Sarabia-Sainz et al, 2011). Other factors, such as water activity, intrinsic properties of protein and sugar, and the amino group-reducing sugar ratio, influence the yields and types of the Maillard reaction products.…”
Section: Characterization Of Bsa-lacmentioning
confidence: 99%